Histopathologic patterns of pancreatic lesions induced by Eurytrema coelomaticum in cattle from the central-west region of the State of Parana, Southern Brazil - Headley, Selwyn A.; Saut, João P.E.; Bassani, Clovis A.; Sangioni, Luis A.; Birgel Junior, Eduardo H.; Yamamura, Milton H. (Brazilian Journal of Veterinary Pathology, 2009)
Bovine eurytrematosis in Brazil is induced by Eurytrema coelomaticum and is endemic in some Brazilian States. The pathology of the disease is not fully understood and there are few descriptions of the histopathological associated lesions. This study analyzed the histopathological patterns of 117 bovine pancreatic samples obtained randomly. Samples were collected during one year from the municipal slaughterhouse of Campo Mourdo, Paran4, Brazil, during routine meat inspection; this location is endemic for bovine eurytrematosis. Five predefined histopathological pattems were analyzed. Differences between the types of lesions were analyzed statistically. The pancreas of 11.97% (14/117) animals was normal; 31.62% (37/117) demonstrated initial proliferative periductal lesions; 17% (21/117) revealed severe proliferative periductal lesions; 21.37% (25/117) were characterized as chronic multifocal interstitial pancreatitis; while 17.09% (20/117) demonstrated chronic diffused interstitial pancreatitis. Statistically cases classified as initial proliferative interductal and chronic multifocal interstitial pancreatitis were the most frequently occurring lesions. The pathogenesis of lesions associated with this disease is also discussed.